Character description in John Webster‘s “The Duchess of Malfi” - Shoyimqulova Mahzuna Shavkatovna (Proceedings of The ICECRS, 2019)
Webster masterly helped to open the way to freedom of women in the society, gender equality, sufferings of the women in patriarchal society must be limited, and characters depicted in the book explicitly and detailed